How replication studies can improve doctoral student education. Issue 1 (February 2023) - Schwab, Andreas; Aguinis, Herman; Bamberger, Peter; Hodgkinson, Gerard P.; Shapiro, Debra L.; Starbuck, William H.; Tsui, Anne S.
In addition to helping advance theory, replication studies offer rich and complementary learning experiences for doctoral students, enabling them to learn general research skills, through the process of striving to imitate good studies. In addition, students gain replication-specific methodological skills and learn about the important roles replications play for making management knowledge trustworthy. We outline best practices for enabling doctoral students and their supervisors to select studies to replicate, execute their replications, and increase the probability of successfully publishing their findings. We also discuss the crucial role of faculty mentors in supporting and guiding replication-based learning of doctoral students. Ultimately, educating doctoral students on how to execute high-quality replication studies helps to answer wider calls for more replication studies in the field of management, an important stepping stone along the journey toward open and responsible research.